Effect of sulphur and zinc fertilization on seed yield, protein, and oil content of sesame (Sesamum indicum L.) in Semi-arid Eastern Plains of Rajasthan - Pinky Yadav; S.S. Yadav; L.R. Yadav; Santosh Choudhary (Annals of Agricultural Research, 2022)
A field experiment was conducted at Sri Karan Narendra Agriculture University, Jobner, Jaipur (Rajasthan) during kharif season of 2018 to determine the effect of sulphur (S) and zinc (Zn) application on crop yield and quality of sesame. Four levels each of sulphur (0, 15, 30 and 45 kg/ha-1) and zinc (0, 10, 20 and 30 kg zinc sulphate/ha-1) were tested in factorial randomized block design (FRBD) replicated thrice. The results revealed that application S and Zn had significant effect on seed yield, oil and protein content of sesame. The seed yield and quality parameters of sesame were enhanced with increasing S and Zn application rates. The highest seed yield (723 kg ha-1), protein (21.5%) and oil content (51.6%) observed with application of S @ 45 kg ha-1 followed by 40 kg S ha-1. In case of Zn, application of zinc sulphate @ 30 kg ha-1 recorded higher seed yield (749 kg ha-1), protein (21.5%) and oil content (50.6%) followed by 20 kg Zn ha-1 . Though, all studied parameters showed increment with increasing dose of S and Zn; however 30 kg S and 20 kg Zn ha-1 were statistically superior to their other respective doses.